Outcomes and Prognosis Prediction of Intermediate Phase Patients in Lampang Province - Phanpunplook, Khemintra; Pongnikorn, Donsuk; Wonghan, Sawitree; Somrit, Waranya (Journal of The Department of Medical Services, 2023)
Background: Intermediate care service is an important part of the patient care process, especially in patients who have passed the critical period but still have abnormal body function or limited performance in day-to-day activities. Objective: This study aimed to examine functional outcomes and prognosis prediction after rehabilitation programs in intermediate care service in Lampang Province. Method: This study focused on prognostic research with a retrospective collection of data of 3 patient groups (stroke, traumatic brain injury and spinal cord injury) who received rehabilitation programs at public hospitals in Lampang (from 1 January 2019 to 31 December 2020). The Barthel index of each patient was collected before and after the rehabilitation period, which was about 6 months from the onset of illness. Results: The results of this study revealed that there was a total number of 1,216 patients (traced in intermediate care process) who participated in a rehabilitation program for 6 months. The Barthel index scored had an increase of 7.1 (95%CI 6.8, 7.5) on average after the rehabilitation. The total Barthel index score also showed a significant difference (p < .001) when analyzed among each intermediate care service pattern and among each initial functional ability group to perform day-to-day activities. Nevertheless, there was no significant difference in the total Barthel index score (p = .479) when analyzing each patient group (spinal cord injury, stroke, and traumatic brain injury). Conclusion: Rehabilitation programs in intermediate care service help increase the functional ability to perform daily life activities in patients, and they have significantly different results (among each intermediate care service pattern and in each initial functional ability group to perform adily life activities). The prognosis prediction model can be used to guide healthcare professionals and individuals regarding their decision on making further management. Finally, the result of this study may be used to improve intermediate care systems in Lampang province in the future.